A proteção integral à criança refugiada - Sponton, Leila Rocha (2018)
The present research aims to address the issue of child refugee and how to implement the principle of integral protection and the guarantee of their fundamental rights. The 21st century has experienced an explosion of refugees around the world, as it has not been seen since the end of World War II. There is no doubt that the children are among the most affected people by the forced exit of their homes. Traumas suffered by a child are visualized in a deeper way and with far more serious and devastating consequences when compared to adults. The situation is even more complicated when this child enters another country unaccompanied or separated from their parents. In addition to absence, the lack of documentation and legal representation often leads to the abandonment of the most basic fundamental rights, such as health, education and work. Throughout this paper we intend to present the historical evolution of international refugee law and the relationship with the children’s rights, as well as the work of international organizations such as UNHCR in the protection of this population, especially children. In addition, this paper aims to discuss the reasons for persecution that justify the recognition of refugee status, always bringing, of course, the child's perspective. Furthermore, apart from the general reasons for persecution, there are some forms that are specific applied to children, such as forced recruitment, child trafficking, sexual exploitation and female genital mutilation, among other practices. We also deal with the legal protection of the child refugee in Brazil and the legislative gaps on the subject and finally we present the issues that most affect child refugee when they enter Brazil and how the State and society must act in order to protect fundamental rights to these children. We understand that Brazil is a country with extensive legislation on the subject of refugees; however, when we specifically address children, we realize that there is still a long way to go, not only in terms of legislation but also in the awareness of society, which still sees the refugee with great prejudice, which makes integration and the enforcement of rights difficult. Thus, the present study pursued to present the difficulties experienced by child refugees when they entered Brazil, as well as to offer alternatives to guarantee the effective protection of these children